2010
DOI: 10.1002/eji.201040518
|View full text |Cite
|
Sign up to set email alerts
|

NOD1 and NOD2 regulation of pulmonary innate immunity to Legionella pneumophila

Abstract: The role of nucleotide‐binding oligomerization domain‐1 (NOD1) and nucleotide‐binding oligomerization domain‐2 (NOD2), cytoplasmic receptors which detect bacterial cell wall molecules, in pulmonary innate immune responses is poorly understood. We determined that both NOD1 and NOD2 detect heat‐killed Legionella and stimulate NF‐κb and IFN‐β promoter activity using an in vitro luciferase reporter system. We next infected NOD1‐ and NOD2‐deficient animals with aerosolized Legionella pneumophila. At 3 days post inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 46 publications
1
75
0
2
Order By: Relevance
“…The noninflammasome NLRs NOD1 and NOD2 are stimulated during L. pneumophila infection. This has been shown in the context of lung infection of knockout mice and infected BMD macrophages obtained from knockout mice as well as a human epithelial cell line (33,(40)(41)(42)(43). The activation of the MAPK and NF-B pathways is in part dependent upon NOD signaling, which is contingent upon RIP2 (44,45).…”
Section: Resultsmentioning
confidence: 89%
“…The noninflammasome NLRs NOD1 and NOD2 are stimulated during L. pneumophila infection. This has been shown in the context of lung infection of knockout mice and infected BMD macrophages obtained from knockout mice as well as a human epithelial cell line (33,(40)(41)(42)(43). The activation of the MAPK and NF-B pathways is in part dependent upon NOD signaling, which is contingent upon RIP2 (44,45).…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, active induction of predominantly Th2 responses via cytosolic recognition of peptidoglycans by Nod 1 and Nod2 was demonstrated in in vivo studies (52,53). Furthermore, L. pneumophila-derived peptidoglycans were shown to activate Nod1 and Nod2 (10,54). Both Nod1 and Nod2 activate NF-kΒ-signaling pathways through the adapter serine-threonine kinase Rip2 and MAPK through CARD9.…”
Section: Discussionmentioning
confidence: 98%
“…L. pneumophila modulates the host cell via cytosolic injection of virulence factors through its Icm/Dot type IV secretion system (T4SS) (5), which enables the bacterium to replicate in a specialized nondegradative vacuole (6). It triggers transmembrane TLRs (7,8), as well as cytosolic NLRs (9,10), and induces a potent inflammatory response, leading to the subsequent initiation of a robust adaptive immune response in the host. Abs of the IgG and IgA isotype were shown to protect from L. pneumophila infection, and CD4 T cells were crucial for Ab isotype switch (11,12).…”
mentioning
confidence: 99%
“…The CARD domain of NOD1 binds the CARD domain of RIP2 through homophilic CARD-CARD interactions (Correa et al, 2012) and induces NFkB. Several studies have shown that NOD1 detects the minimal tri-DAP structure of Gramnegative bacteria, including Salmonella typhimurium, Legionella pneumophila, and Shigella flexneri (Berrington et al, 2010;Keestra et al, 2011;Robertson and Girardin, 2013). In order to examine whether Salmonella infection activates chNOD1 signaling in chicken, Salmonella enteritidis was used to infect Qingyuan partridge chickens.…”
Section: Discussionmentioning
confidence: 99%